Badania laboratoryjne przewodnictwa cieplnego piasku kwarcowego = Labdratory tests of quartz sand thermal conductivity - Gontaszewska-Piekarz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Thermal conductivity is the most important parameter in calculation of earth heat absorbing. There is an absence of wide investigations in this range. This paper presents description of thermal conductivity measurements in quartz sands from Osiecznica. Methodology and measurement equipment were precisely discussed. Obtained results were compared with results from literature.
Keywords: przewodnictwo cieplne; grunty; geotermia; thermal conductivity; grounds; geothermy